Cuban Agriculture Before 1959: The Social Situation - José Alvarez (EDIS)
Very few studies of social indicators were carried out in Cuba before 1959. The two most complete included the 1946 National Agricultural Census (Memoria, 1951) and the 1953 Population, Housing, and Electoral Census (Oficina, 1954-55). In 1956-1957, the University Catholic Association (Agrupación Católica Universitaria, ACU) conducted a national survey (Gastón et al., 1957; the original Spanish version can found at http://edis.ifas.ufl.edu/FE292 and the English translation at http://edis.ifas.ufl.edu/FE297) that, despite the existing critiques discussed below, seemed to confirm the findings of the two censuses. Jolliffe et al. (1958) is perhaps the most quoted study on pre-1959 research on nutrition but, as explained below, it refers to a narrow universe. Díaz-Briquets (1983; 1986) contain useful information on several of the variables discussed in this fact sheet. This is EDIS document FE480, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.